Application Activity Numeracy Pleasant Through Snakes and Ladders Game at SDN 2 Tilongkabila - Fatma Riyanti Sanggulu; Sri Ayu B. Angio; Andarista Puni (Global Scientific Publishing, 2023)
For increase ability number of participants educate , one method that can used that is application activity numeracy through game snake stairs which is method learning that has characteristics integrate between the learning process and play . Research methods used _ is Classroom Action Research (PTK) with using the spiral model by Kemmis and McTaggart. Research result showing that before implementation cycle only there were 5 out of 15 participants educate or amounting to 33.33% of participants educate those already show behavior numerated , in cycle I obtained as many as 8 out of 15 participants educate or amounting to 53.33% already show behavior numerate . Implementation actions in cycle II were obtained as many as 14 of the 15 participants educate or amounting to 93.33% already show behavior numerate . Based on the data above , this happens change behavior on each implementation cycle , increase from implementation observation initial which was initially 33.33% to cycle I increased by 53.33% of participants educate who shows behavior numerate . Next , improvement behavior numerate on implementation action cycle I to cycle II , namely by 40% of cycle I to cycle II. This matter show that application activity numeracy pleasant through game snake ladder can increase behavior numerate participant educate 4th grade at SDN 2 Tilongkabila .
Keywords: numerate; participant; application; pleasant